2021
DOI: 10.1523/jneurosci.0195-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Heat But Not Mechanical Hypersensitivity Depends on Voltage-Gated CaV2.2 Calcium Channel Activity in Peripheral Axon Terminals Innervating Skin

Abstract: Title: Heat but not mechanical hypersensitivity depends on voltage-gated Ca V 2.2 calcium channel activity in peripheral axon terminals innervating skin Abbreviated title: Peripheral Ca V 2.2 channels control heat hypersensitivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 111 publications
8
44
0
Order By: Relevance
“…Ca v 2.2 plays a crucial role in AP-induced transmitter release in the dorsal horn ( Jevtovic-Todorovic and Todorovic, 2006 ; Yu et al, 2008 ). It has been reported that Ca v 2.2 also participates in TRPV1-mediated thermal hypersensitivity in peripheral axons innervating the skin ( DuBreuil et al, 2021 ). Consistent with this study, we observed that i. pl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca v 2.2 plays a crucial role in AP-induced transmitter release in the dorsal horn ( Jevtovic-Todorovic and Todorovic, 2006 ; Yu et al, 2008 ). It has been reported that Ca v 2.2 also participates in TRPV1-mediated thermal hypersensitivity in peripheral axons innervating the skin ( DuBreuil et al, 2021 ). Consistent with this study, we observed that i. pl.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, pharmacological blockade of Ca v 2.2 does not attenuate mechanical hypersensitivity in CFA-induced mice ( Pitake et al, 2019 ). Ca v 2.2 KO mice show a comparable mechanical sensation as WT animals do ( Pitake et al, 2019 ; DuBreuil et al, 2021 ) but exhibit markedly reduced mechanical hypersensitivity following spinal nerve ligation ( Saegusa et al, 2001 ). Our work shows that while CVB-D and Z944 have potent analgesic effects against mechanical hypersensitivity in carrageenan- and CFA-induced mouse models ( Figures 1D,G,H , Figure 6D,F,I and Supplementary Figure S5E ), SNX-111 does not alleviate mechanical hypersensitivity in carrageenan-induced mice ( Figure 7G ) and administration of SNX-111 together with CVB-D or Z944 produces negligible synergistic or additional analgesia ( Figures 7H,I ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds or ligands that influence the activity of presynaptic N-type channel have consequences on the release of neurotransmitter, in the transmission of pain signalling from the periphery to the central nervous system (Snutch, 2005) and perhaps in the peripheral sensory thermoreceptors outside the spinal cord (DuBreuil et al, 2021). A direct inhibition of Ca v 2.2 impairs the activity of a special subset of neurons, including pain-sensing primary nociceptors (Miljanich, 2004) and might play a role in heat hypersensitivity induced by chronic neuropathic conditions (DuBreuil et al, 2021). A reduction of calcium ion influx into hyperactivated neurons via inhibition of Ca v 2.2 can be expected to cause attenuation of hyperexcitation.…”
Section: Discussionmentioning
confidence: 99%
“…Ca v 2.2 channels are expressed in high density in primary somatosensory afferent neurons, in the dorsal horn, specifically in the superficial laminae I and II, and are also expressed in the ventral horn (Gohil et al, 1994; Yusaf et al, 2001). They are especially distributed along the dendrites and preferentially at presynaptic terminals, contributing to the release of glutamate, substance P and calcitonin gene‐related peptide (CGRP; DuBreuil et al, 2021), which activate postsynaptic receptors in the membrane of spinothalamic neurons. Ca v 2.2 channels are important contributors to synaptic transmission in ascending pain pathways.…”
Section: Introductionmentioning
confidence: 99%